2001
DOI: 10.1001/archneur.58.1.91
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Methylprednisolone Therapy in Multiple Sclerosis Induces Apoptosis in Peripheral Blood Leukocytes

Abstract: Corticosteroid pulse therapy is a strong inducer of leukocyte apoptosis. Induction of apoptosis might contribute to the down-regulation of T-cell activity and thereby terminate inflammation in the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 40 publications
(48 reference statements)
9
73
1
1
Order By: Relevance
“…In the human MNCs, the CD3-positive T-cells also preferentially underwent mafosfamide-induced apoptosis. The higher variability of early apoptotic and late apoptotic/necrotic cellular changes in the human MNCs was to be expected and can at least partly be explained by the glucocorticosteroid treatment that each patient had received perioperatively before blood donation (Leussink et al, 2001). Additional attempts to yield more stable proportions of viable and dying MNCs, e.g., by addition of IL-2 or stimulation of the T-cell receptor, did not result in significant changes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the human MNCs, the CD3-positive T-cells also preferentially underwent mafosfamide-induced apoptosis. The higher variability of early apoptotic and late apoptotic/necrotic cellular changes in the human MNCs was to be expected and can at least partly be explained by the glucocorticosteroid treatment that each patient had received perioperatively before blood donation (Leussink et al, 2001). Additional attempts to yield more stable proportions of viable and dying MNCs, e.g., by addition of IL-2 or stimulation of the T-cell receptor, did not result in significant changes.…”
Section: Discussionmentioning
confidence: 90%
“…Also, the phagocytic capacity of the individual microglial cells as reflected by the phagocytic index in the nonmafosfamide-exposed MNC amounted to only 64.5% in comparison with the apoptotic target cell population. Baseline microglial phagocytosis of nonmafosfamide-treated MNC can at least partly be explained by the varying proportions of apoptotic cells inevitably present in the MNC of the corticosteroid-treated patients, which were prone to undergo apoptosis spontaneously (Leussink et al, 2001).…”
Section: Human Adult Microglia Phagocytoses Autologous Apoptotic Perimentioning
confidence: 99%
“…There are numerous in vivo and in vitro reports on corticosteroids and their analogues which effect thymocyte apoptotsis and which also have adverse effects on peripheral T cell activation events. [76][77][78][79][80][81][82] However, a previous study by Wienberg et al 34 demonstrated that TREC levels increased in cord blood transplant recipients even while receiving low-dose steroids as GVHD prophylaxis. However, this data does not exclude the possibility that high dose corticosteroids used in GVHD treatment would have an adverse effect on thymic output.…”
Section: Discussionmentioning
confidence: 97%
“…GC are widely used to treat acute relapses in MS patients by exploiting their potent pro-apoptotic and anti-inflammatory activity [38,39]. Previously we had identified peripheral T lymphocytes as essential targets but the specific role of GC actions on T effector cells remained elusive.…”
Section: Discussionmentioning
confidence: 99%